Development of reference transcriptomes for the major field insect pests of cowpea: a toolbox for insect pest management approaches in West Africa - Agunbiade, T.A.; Sun, W.; Coates, B.S.; Djouaka, R.F.; Tamo, Manuele; Ba, Malick N.; Binso-Dabire, L.; Baoua, I.; Olds, B.P.; Pittendrigh, Barry Robert (Public Library of Science, 2013)
Cowpea is a widely cultivated and major nutritional source of protein for many people that live in West Africa. Annual yields and longevity of grain storage is greatly reduced by feeding damage caused by a complex of insect pests that include the pod sucking bugs, Anoplocnemis curvipes Fabricius (Hemiptera: Coreidae) and Clavigralla tomentosicollis Stål (Hemiptera: Coreidae); as well as phloem-feeding cowpea aphids, Aphis craccivora Koch (Hemiptera: Aphididae) and flower thrips, Megalurothrips sjostedti Trybom (Thysanoptera: Thripidae). Efforts to control these pests remain a challenge and there is a need to understand the structure and movement of these pest populations in order to facilitate the development of integrated pest management strategies (IPM). Molecular tools have the potential to help facilitate a better understanding of pest populations. Towards this goal, we used 454 pyrosequencing technology to generate 319,126, 176,262, 320,722 and 227,882 raw reads from A. curvipes, A. craccivora, C. tomentosicollis and M. sjostedti, respectively. The reads were de novo assembled into 11,687, 7,647,10,652 and 7,348 transcripts for A. curvipes, A. craccivora, C. tomentosicollis and M. sjostedti, respectively.Functional annotation of the resulting transcripts identified genes putatively involved in insecticide resistance, pathogen defense and immunity. Additionally, sequences that matched the primary aphid endosymbiont, Buchneraaphidicola, were identified among A. craccivora transcripts. Furthermore, 742, 97, 607 and 180 single nucleotide polymorphisms (SNPs) were respectively predicted among A. curvipes, A. craccivora, C. tomentosicollis and M.sjostedti transcripts, and will likely be valuable tools for future molecular genetic marker development. These results demonstrate that Roche 454-based transcriptome sequencing could be useful for the development of genomic resources for cowpea pest insects in West Africa.